Locating an Intergenerational Self in Postcolonial Family Histories. Issue 4 (2nd October 2017) - Barnwell, Ashley
ABSTRACT: Historians acknowledge that since the 1970s family history research has driven individuals to confront the silences within Australia's colonial past, including 'the convict stain'. However, little attention is given to how the practice has been used by the Stolen Generations to deal with the fracturing impact of 'protectionist' social policies on family and life histories. To explore this, I bring the concept of the intergenerational self into dialogue with 'Paul's Story', a short memoir collected in Carmel Bird's The Stolen Children: Their Stories (1998), and singer/songwriter Archie Roach's testimony from the ABC Blackout television documentary 'Best Kept Secret' (1991). In these cases, the narrative continuity of family lines is severed. Faced with lost origins, the authors must reclaim an intergenerational self retrospectively through research and revision. The paper examines these cases in the context of an emerging focus on relational lives. It demonstrates how people write and tell family histories to rebuild an intergenerational identity in the wake of destructive colonial policies.